Смоляне - Герои Советского Союза - Воробьев М. В. (Книжное издательство, 1963)
Экземпляры: КХ (20140626) / Инвентарный номер: 348807 / Цена: 0.98 / Сис.шифр: 9(С)27 / Авт.знак: В 75 / ГРНТИ: 03 / ББК: 63